From Cultured Vascular Cells to Vessels: The Cellular and Molecular Basis of Vascular Dysfunction in Space - Locatelli, Laura; Castiglioni, Sara; Maier, Jeanette A. M. (Frontiers in Bioengineering and Biotechnology, 2022)
Life evolved on this planet under the pull of gravity, shielded from radiation by the magnetosphere and shaped by circadian rhythms due to Earth’s rotation on its axis. Once living beings leave such a protective environment, adaptive responses are activated to grant survival. In view of long manned mission out of Earth’s orbit, it is relevant to understand how humans adapt to space and if the responses activated might reveal detrimental in the long run. Here we review present knowledge about the effects on the vessels of various extraterrestrial factors on humans as well as in vivo and in vitro experimental models. It emerges that the vasculature activates complex adaptive responses finalized to supply oxygen and nutrients to all the tissues and to remove metabolic waste and carbon dioxide. Most studies point to oxidative stress and mitochondrial dysfunction as mediators of vascular alterations in space. Unraveling the cellular and molecular mechanisms involved in these adaptive processes might offer hints to design proper and personalized countermeasures to predict a safe future in space.